Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Find the Laurent expansion for $$\frac{\exp(\frac 1{z^2})}{z-1}$$ about $z=0$. I know that $\exp( \frac 1{z^2}) = \sum_{n=0}^\infty \frac{z^{-2n}}{n!}$ and $ \frac 1{z-1}=-\sum_{n=0}^\infty z^n$

share|improve this question
    
And do you know how to multiply power series: en.wikipedia.org/wiki/Power_series#Multiplication_and_division ? –  Dirk Mar 20 '12 at 8:07
    
I was thinking of that but I was having difficult time simplifying it and finding a direct formula for the coefficients. Does it matter that the power series we are multiplying have different powers of z because in the given example they both have (x-c)^n –  caligurl11 Mar 20 '12 at 13:42
add comment

2 Answers 2

Write $$\exp(1/z^2) = \sum_{n=-\infty}^\infty a_n z^n \qquad\text{and}\qquad \frac{1}{z-1} = \sum_{n=-\infty}^\infty b_n z^n,$$ i.e. $a_{-2n} = 1/n!$ and $a_k = 0$ otherwise, and $b_n = -1$ for $n \ge 0$ and $b_n = 0$ for $n < 0$. Multiply the two series: $$ \left(\sum_{n=-\infty}^\infty a_n z^n\right)\left(\sum_{n=-\infty}^\infty b_n z^n\right) = \left(\sum_{n=-\infty}^\infty c_n z^n\right)$$ and start identifying the $c_n$:s. We get $$ c_0 = a_0 b_0 + a_{-2}b_2 + a_{-4}b_4 + \cdots = -\left( \frac1{0!} + \frac{1}{1!} + \frac1{2!} + \cdots \right) = -e,$$ $$ c_1 = a_0 b_1 + a_{-2}b_3 + a_{-4}b_5 + \cdots = -\left( \frac1{0!} + \frac{1}{1!} + \frac1{2!} + \cdots \right) = -e,$$ etc. In other words, $c_n = -e$ for all $n \ge 0$. For the negative indices you get $$ c_{-1} = a_{-2} b_1 + a_{-4}b_3 + a_{-6}b_5 + \cdots = -\left( \frac{1}{1!} + \frac1{2!} + \frac1{3!}+ \cdots \right) = -(e-1),$$ $$ c_{-2} = a_{-2} b_0 + a_{-4}b_2 + a_{-6}b_4 + \cdots = -\left( \frac{1}{1!} + \frac1{2!} + \frac1{3!}+ \cdots \right) = -(e-1),$$ $$ c_{-3} = a_{-4} b_1 + a_{-6}b_3 + a_{-8}b_5 + \cdots = -\left( \frac{1}{2!} + \frac1{3!} + \frac1{4!}+ \cdots \right) = -(e-1-1),$$ $$ c_{-4} = a_{-4} b_0 + a_{-6}b_2 + a_{-8}b_4 + \cdots = -\left( \frac{1}{2!} + \frac1{3!} + \frac1{4!}+ \cdots \right) = -(e-1-1).$$

By now, the pattern should be obvious, if $n = -2k$, $$ c_{-2k} = c_{-2k+1} = - \left(e - 1 - \frac1{1!} - \frac1{2!} - \cdots \frac1{k!}\right) = -e + \sum_{j=0}^k \frac{1}{j!}.$$

share|improve this answer
    
perfect answer! thanks a lot. –  d13 May 6 '13 at 13:09
add comment

I have not read the previous anwer in detail. The short cut way is to notice the relationship that $$f^{n}=\frac{n!}{2\pi i}\oint \frac{f(z)dz}{(z-c)^{n+1}}$$

Notice that for Laurent series we have $$a_{n}=f^{n}/n!=\frac{1}{2\pi i}\oint \frac{f(z)dz}{(z-c)^{n+1}}$$

Thus the Laurent series coefficient for $f=\frac{e^{z^{-2}}}{z-1}$ is $$a_{n}=\frac{1}{2\pi i}\oint \frac{e^{z^{-2}}dz}{z^{n+1}(z-1)}$$

Consider the Cauchy integral formula which says $$f(c)=\frac{1}{2\pi i}\oint \frac{f(z)dz}{z-c}$$

Thus let $$g=\frac{e^{z^{-2}}}{z^{n+1}}, a_{n}=g(1)=e$$ should suffice. I might be wrong somewhere though.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.